Sonochemical synthesis of CuO nanostructures and their morphology dependent optical and visible light driven photocatalytic properties - Pandiyarajan, Thangaraj; Saravanan, Rajendran; Karthikeyan, Balasubramanian; Gracia, Francisco; Mansilla, Héctor D.; Gracia Pinilla, Miguel Ángel; Mangalaraja, Ramalinga Viswanathan (2016)
A controlled synthesis of CuO nanostructures with various morphologies were successfully achieved by presence/absence of low frequency (42 kHz) ultrasound with two different methods. The size, shape and morphology of the CuO nanostructures were tailored by altering the ultrasound, mode of addition and solvent medium. The crystalline structure and molecular vibrational modes of the prepared nanostructures were analysed through X-ray diffraction and FTIR measurement, respectively which confirmed that the nanostructures were phase pure high-quality CuO with monoclinic crystal structure. The morphological evaluation and elemental composition analysis were done using TEM and EDS attached with SEM, respectively. Furthermore, we demonstrated that the prepared CuO nanostructures could be served as an effective photocatalyst towards the degradation of methyl orange (MO) under visible light irradiation. Among the various nanostructures, the spherical shape CuO nanostructures were found to have the better catalytic activities towards MO dye degradation. The catalytic degradation performance of MO in the presence of CuO nanostructures showed the following order: spherical\nanorod \layered oval \nanoleaf \triangular \shuttles structures. The influence of loading and reusability of catalyst revealed that the efficiency of visible light assisted degradation of MO was effectively enhanced and more than 95 % of degradation was achieved after 3 cycles